Evaluation of Uniblends and Biblends of Commercial Maize Hybrids - Krishna, K. Murali; Laxminarayana, P.; Chikkappa, G. K.; Rao, P. Sambasiva; Dangi, Kuldeep Singh; Shahi, J. P.; Kulkarni, N. (International Journal of Bio-resource and Stress Management, 2018)
Hybrid mixtures have been suggested as a mean to achieve increased crop productivity. Eight medium-season commercial maize (Zea mays L.) hybrids of public as well as private sectors were evaluated as uniblends as well as all possible biblends arrived by mixing equal quantity of seed in RCBD with three replications, during rabi, 2015 at Student’s farm, College of Agriculture, Rajendranagar, Hyderabad. Data were recorded for grain yield and its components. Three uniblends viz., DHM-117, DHM-121 and SUNKRANTHI recorded highly significant positive general mixing ability effects for grain yield and the yield contributing characters. These uniblends can be used to develop high yielding hybrid mixture combinations and as a base population for further improvement. Among 28 combinations, four biblends viz., DHM-117×SUN KRANTHI and DHM-121×SUN KRANTHI, GK-3153×NMH-731 and GK-3063×GK-3153 recorded high per se of 15.59-21.41 percent and expressed significant competitive ability over the high yielding uniblends. In general, the high yielding biblends involved at least one high yielding uniblend. Cross-pollination boost to seed yield was found to be greater from two hybrids which have different parentage or sources. Diallel analysis of mixing ability analogous to genetic analysis of combining ability demonstrated that uniblends differed in their ability to determine grain yield in biblends. The ability to predict biblend performance based on uniblend performance, together with the potential for above average grain yield, suggested that biblends can be formulated to achieve specific production requirements.